A Population-Based Cohort Study on the Association of Hyperthyroidism With the Risk of Hyperlipidemia and the Effects of Anti-thyroid Drugs on Hepatic Gene Expression - Wu, Tien-Yuan; Wang, Chung-Hsing; Tien, Ni; Lin, Cheng-Li; Chu, Fang-Yi; Chang, Hsiao-Yun; Lim, Yun-Ping (Frontiers in Medicine, 2020)
There have been no reports on the association of hyperthyroidism with hyperlipidemia in patients undergoing treatment especially in Asia. To determine the association between hyperthyroidism and the risk of hyperlipidemia in patients, we conducted a retrospective cohort study using Longitudinal Health Insurance Database (LHID) from Taiwan, R.O.C. We also evaluate the influence of 6-n-propyl-2-thiouracil (PTU) and methimazole (MMI) on hepatic genes to explain changes in blood lipid levels in a hepatic cell line model. The cohort study involved 13,667 patients with hyperthyroidism, and the corresponding comparison cohort had four times as many patients. Using Kaplan-Meier analysis method, the results showed that, compared to patients without hyperthyroidism, the overall incidence of hyperlipidemia was significantly higher in the hyperthyroidism patients (18.7 vs. 11.8 cases/1,000 persons-years; adjusted HR 1.5; 95% CI, 1.41–1.59). With only PTU or MMI/carbimazole (CBM) treatment, patients with hyperthyroidism showed a 1.78-fold (95% CI, 1.50–2.11) and 1.43-fold (95% CI, 1.27–1.60) higher risk of hyperlipidemia than those without hyperthyroidism, respectively. Additionally, hyperthyroidism patients that received surgery only or surgery with I131 therapy tended to have a higher risk of hyperlipidemia. Although PTU and MMI treatment decreased the expression levels of genes responsible for circulating remnant lipoproteins, they increased the levels of lipogenic gene expression in hepatic cells. Thus, treatment of hyperthyroid patients with anti-thyroid drugs (ATDs), I131, or surgery is likely to induce hyperlipidemia. ATDs downregulate the expression of genes involved in lipoproteins clearance; increases lipogenic genes expression, which may partly contribute to abnormal blood lipid profiles.